Residual oil removal from oil palm empty fruit bunches using high pressure water spray system - Md Yunos, Noor Seribainun Hidayah (2015)
Oil extraction rate (OER) is one of the key factor in evaluating the performance and efficiency of the palm oil mill by comparing the ratio of oil palm produced per day with the total fresh fruit bunches (FFB) processed per day. Under Palm Oil National Key Economic Area, Malaysia is expected to achieve OER value up to 23% in the year 2020. One of the strategies to achieve this goal is to study the potential of recovering the residual oil from oil palm biomass which is oil palm empty fruit bunches (OPEFB). Hence, this study is aimed to develop a baseline study of the characterisation and localisation of the residual oil on the fiber and also to investigate the effects of the hydrothermal method on the yield and quality of the oil as well as structures of the fibers. A new method called High Pressure Water Spray System (HPWSS) was introduced and performed by spraying pressurized water (500 psi) at 30°C, 60°C, and 90°C and combination of watersteam at 120°C and 150°C onto the surface of the OPEFB. Soxhlet extraction and palm oil tester were used to recover the residual oil on the different parts of fiber (spikelet, stalk and press-shredded) and to determine the qualities of the residual oil. The baselines studies show that the highest residual oil found was on the spikelet (7.39±3.45%) followed by press-shredded OPEFB (3.61±0.34%) and lastly stalk fiber (2.04±2.31%). This result was in agreement with the Sudan dye analyses. The initial residual oil of OPEFB contains a higher amount of valuable carotenes (409.02 ppm), comparable values of Deterioration of Bleach ability Index (DOBI) (2.42), Peroxide Value (PV) (1.84 meq/kg), and fatty acid compositions in comparison to the raw crude palm oil (CPO) from the mill. The experimental results of HPWSS indicated that, the highest oil yield was achieved at 150°C (94.41±0.02%) followed by 120°C (86.14±0.03%), 90°C (80.54±0.02%), 60°C (70.37±0.21%) and 30°C (63.24±0.58%), respectively. The residual oil exhibit better quality of Free Fatty Acid (FFA) (6.21±0.35%), DOBI (2.42±0.23), PV (4.89±0.27meq/kg), phosphorus content (6.87±0.71 ppm) and iron content (3.43±0.35 ppm) at 30°C compared to 150°C where the values of FFA, DOBI, PV,phosphorus, and iron content were (7.79±0.77%), (1.63±0.38), (5.85±0.60 meq/kg), (11.70±0.61 ppm), and (7.17±0.15 ppm), respectively. From the gas chromatography-flame ion detector (GC-FID) analyses, similar fatty acid composition of the residual oil at each treatment temperature was observed. This result was in agreement with the spectroscopy graph obtained from Fourier transform infrared (FTIR). Lignocellulosic content analyses revealed some increment of cellulose content in the OPEFB (39.1%) while major decrement of hemicellulose content (19.80%) and lignin content (22.43%) was discovered after HPWSS treatment at 150°C. Scanning electron microscopy (SEM) and nitrogen adsorption analysis (BET) analyses showed smoother surface, higher surface areas,higher total pore volume and lower pores diameter as the temperature of HPWSS increased. Based on the results obtained, the residual oil was considered as low quality oil and cannot be consumed as edible oil. Nevertheless, this residual oil still can be used for non-edible applications such as soap, cosmetics, bio-lubricant and bio-diesel. The residual OPEFB fiber can be used as a feedstock for bioconversion applications. Therefore, the HPWSS is a promising technique believed to be useful for the removal of residual oil from OPEFB.